Duplicated common bile duct with pancreatic adenocarcinoma - Kapoor, Atul; Kapur, Aprajita; Mahajan, Goldaa; Sharma, Shailender (International Surgery Journal, 2025)
A 42-year-old South Asian male presented to our hospital with anorexia, abdominal pain, and jaundice. Abdominal ultrasonography revealed a 3.5×3.5 cm hypoechoic solid mass in the pancreatic head with central necrosis, resulting in dilatation of the proximal common bile duct, main pancreatic duct, and intrahepatic biliary system. Magnetic resonance cholangiopancreatography (MRCP) confirmed the ultrasonographic findings and identified complete duplication of the biliary system with a mildly dilated duplicated common bile duct that exhibited pancreaticobiliary maljunction (PBM) with narrowing and was opening into the main pancreatic duct at the pancreatic body level. Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) of the pancreatic mass revealed adenocarcinoma. This case illustrates the rare occurrence of a duplicated common bile duct (DBCD) associated with a pancreatic head mass, underscoring the need for comprehensive imaging and a multidisciplinary approach in the management of complex hepatopancreatic biliary pathologies. This case also suggests a modification to the existing Choi classification of DBCD to include PBM anomalies. Further research is required to understand the long-term outcomes of these anatomical variations in pancreatic malignancies.